Charting physiotherapy students' attitudes toward people with chronic pain as they progress through their undergraduate programme: An observational study. (18th November 2022) - Mankelow, Jagjit; Ryan, Cormac G.; Morris, Hayley; Lauchlan, Douglas; Seenan, Christopher; Taylor, Paul; Martin, Denis
ABSTRACT: Background: Healthcare professionals' attitudes toward people with chronic pain influence their clinical practice. Objectives: To investigate physiotherapy students' attitudes and beliefs toward people with chronic pain over the course of their Scottish undergraduate program. Methods: In this observational study, physiotherapy students from one university were recruited in the first year and followed up to their final year (year 1 n = 62/75, year 2 n = 68/72, year 3 n = 59/69, year 4 n = 74/74) for 4 years. The Health-Care Providers' Pain and Impairment Relationship Scale (HC-PAIRS with scores ranging from 15 to 105) was completed annually Results: A one-way ANOVA found that attitudes and beliefs improved significantly ( p < .01) from the first to final year (9.2 ± 11.5 (mean±SD)). Participants showed a reduction in scores (signifying improved attitudes) annually with smaller reductions initially followed by a larger reduction in the final 2 years. Conclusions: This is the first study to chart changes in the same cohort of physiotherapy students' attitudes and beliefs toward people with chronic pain over time. Future work should explore which aspects of degree courses, if any, impact upon attitudes and beliefs toward people with chronic pain so that courses can be enhanced accordingly.